Pembentukan Akhlak Berlandaskan Keimanan : Landasan Filosofis-Teologis Dalam Kurikulum PAI Pada Mata Pelajaran Aqidah Akhlak di Madrasah Ibtidaiyah - Awwalina, Linlin Sabiqa (Perkumpulan Peneliti dan Pegiat Literasi, 2023)
The dynamic development of the curriculum is essential to addressing the demands of contemporary times and Islamic education. However, the implementation of an independent curriculum, as an effort to simplify the previous one and strengthen the profile of Pancasila students, has not been fully realized in educational institutions, presenting challenges in adapting to current needs. This study aims to innovate the philosophical and theological foundations of aqidah and moral education in Madrasah Ibtidaiyah based on faith. The methodology used is a literature review, collecting data from journals, books, and conferences. The findings reveal that philosophical and theological foundations greatly influence the goals of Islamic education in nurturing individuals with noble character. The formation of tauhid within the family serves as the primary basis for establishing faith, which is a crucial asset in formal education. Teachers play a vital role in delivering materials related to Islamic values using various strategies and methods to integrate knowledge and moral development. By practicing faith in daily life through worship, students can cultivate sincerity in their actions. Therefore, a PAI curriculum grounded in strong philosophical and theological principles can help build morally upright and strong individuals.